2013
DOI: 10.1002/14651858.cd008819.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Compression stockings for the initial treatment of varicose veins in patients without venous ulceration

Abstract: Compression stockings for the initial treatment of varicose veins in patients without venous ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 45 publications
1
50
0
2
Order By: Relevance
“…The evidence is sparse, but class 2 compression stockings seem to be more effective than lower class stockings in the prevention of ulcer recurrence. Consistent with our findings, another review [16] states that the evidence is too sparse to allow firm conclusions about the effects of compression stockings for the initial treatment of varicose veins in patients without ulceration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The evidence is sparse, but class 2 compression stockings seem to be more effective than lower class stockings in the prevention of ulcer recurrence. Consistent with our findings, another review [16] states that the evidence is too sparse to allow firm conclusions about the effects of compression stockings for the initial treatment of varicose veins in patients without ulceration.…”
Section: Discussionsupporting
confidence: 89%
“…Systematic reviews about post-thrombotic syndrome [11][12][13][14] and pain [11] in patients with deep venous thrombosis show uncertain effects. Systematic reviews published in 2013 and 2014 [15,16] question the effects of preventive use of compression stockings for patients with venous insufficiency, but a preliminary search showed that these systematic reviews were no longer up to date. Elderly patients with chronic venous insufficiency and multimorbidity are of particular interest because they frequently need assistance from home care personnel to administer compression stockings.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent Cochrane review (Shingler et al . ), there is still insufficient evidence regarding the effectiveness of compression stockings as the sole and initial treatment for the milder forms of varicose veins. However, the symptoms subjectively improved with the use of compression stockings in studies where symptoms were assessed, which also was expressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…212 Despite the popularity of elastic stockings, evidence of their efficacy is unclear, based on the lack of randomized controlled trials for both superficial venous incompetence and the postthrombotic leg. 213,214 However, there is ample lower quality evidence based on non-RCTs and clinical experience, to suggest their use because they improve patient symptoms 213 and they improve patients' QoL. 215 In general, there are issues putting on and removing elastic stockings, especially in the elderly, which along with the sensation of warmth and deterioration of pre-existing pruritis associated with venous eczema, could account for the suboptimal patient compliance.…”
Section: Chronic Venous Disease Without Ulceration (C0ec4)mentioning
confidence: 99%